Helping Adolescents with Greater Psychosocial Needs: Evaluation of a Positive Youth Development Program - Daniel T. L. Shek; Rachel C. F. Sun (The Scientific World Journal)
The Tier 2 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes), designed and implemented primarily by school social workers, attempts to help adolescents with greater psychosocial needs. After completion of the Tier 2 Program in the Full Implementation Phase (2006/07 school year), 10,255 Secondary 1 students in 207 schools responded to the Subjective Outcome Evaluation Form (Form C) to assess their views of the program, instructors, and perceived effectiveness of the program. Results showed that high proportions of the respondents had positive perceptions of the program and the instructors, and roughly four-fifths of the respondents regarded the program as helpful to them. Pearson correlation analyses showed that perceptions of the program and instructors were significantly correlated with perceived effectiveness of the program. Participants who joined volunteer training activities generally had higher global subjective outcome evaluation scores than did participants who attended programs without volunteer training activities.